2004
DOI: 10.1007/s00018-004-4127-7
|View full text |Cite
|
Sign up to set email alerts
|

Lactacystin-induced apoptosis of cultured mouse cortical neurons is associated with accumulation of PTEN in the detergent-resistant membrane fraction

Abstract: The tumor suppressor function of PTEN is attributed to its phospholipid phosphatase activity that dephosphorylates the plasma membrane phosphatidylinositol-(3,4,5)-triphosphate [PtdIns(3,4,5)P3]. Implicit in this notion is that PTEN needs to be targeted to the plasma membrane to dephosphorylate PtdIns(3,4,5)P3. However, the recruitment of PTEN to the plasma membrane is not fully understood. Here, we demonstrate PTEN accumulation in the detergent-insoluble fraction of neuronal cells in response to treatment by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 19 publications
(17 reference statements)
0
28
0
Order By: Relevance
“…Notably, these inhibitors are selective for calpains and do not target the proteasome, another major proteolytic pathway in cells. In fact, proteasome inhibitors themselves are quite toxic and rapidly trigger activation of caspase-3 and apoptosis in GCs (78 -80) 3 and in other cultured neurons (81)(82)(83)(84).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, these inhibitors are selective for calpains and do not target the proteasome, another major proteolytic pathway in cells. In fact, proteasome inhibitors themselves are quite toxic and rapidly trigger activation of caspase-3 and apoptosis in GCs (78 -80) 3 and in other cultured neurons (81)(82)(83)(84).…”
Section: Discussionmentioning
confidence: 99%
“…Fornai and colleagues (7) and Rideout and coworkers (8) documented that proteasome inhibition can induce apoptosis in DA neurons, whereas Rideout and colleagues (25) and Cheung and coworkers (26) reported that lactacystin activated caspase-3 in cortical neurons, cerebella granule neurons, and sympathetic neurons. Our study provided direct evidence showing that caspase-3 was activated in DA neurons in response to proteasome inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…21,124 In cortical neurons of the central nervous system, Jessica et al 125 analyzed the expression of different AQPs while cells undergo apoptosis induced by treatment with lactacystin, a specific proteasome inhibitor. [126][127][128] These authors found that AQP4 was highly downregulated, suggesting that this aquaporin, considered to be the main water channel in the brain, 129 does not play an important role in the loss of water during AVD. In contrast, overexpression of AQP1, AQP8 and AQP9 was observed after lactacystin treatment.…”
Section: Apoptosis and Aqpsmentioning
confidence: 99%
“…In contrast, overexpression of AQP1, AQP8 and AQP9 was observed after lactacystin treatment. [126][127][128] However, favoring a role for AQP4 in apoptosis, Kong et al 87 observed increased basal apoptosis in adult neural stem cells obtained from KO AQP4 ¡/¡ mice.…”
Section: Apoptosis and Aqpsmentioning
confidence: 99%